Samaritan donation: A new challenge for the Italian transplant community. (30th August 2016) - Ferri, Francesca; Serati, Marta; Colombo, Elisa Maria; Gallo, Francesca; Buoli, Massimiliano
Highlights: "Samaritan donation" is an organ donation to people who do not have any familiar or emotional relationship with the recipient. Samaritan donation is performed when no other forms of living donation is available. We present the case of a 63-year old woman who has been admitted to the first Italian Samaritan donation.